An ERP Study of the Temporal Course of Gender–Color Stroop Effect - Li, Yingli; Du, Juan; Song, Qingfang; Wu, Sina; Liu, Lihong (Frontiers in Psychology, 2021)
Pink and blue colors have been found to associate with gender stereotypes in previous Western studies. The purpose of the present study was to explore the neuropsychological processing basis of this effect in contemporary Chinese society. We presented stereotypically masculine or feminine occupation words in either pink or blue colors to Chinese college students in a modified Stroop paradigm, in which participants were asked to classify each occupation word by gender as quickly and accurately as possible. Event-related potential (ERP) signals were concurrently recorded in order to identify the temporal dynamics of gender stereotypical interference effect. The behavioral results showed that pink-masculine stimuli elicited longer response time and lower accuracy than blue-masculine stimuli in the participants, while no such differences were observed between pink-feminine and blue-feminine conditions. The ERP results further revealed distinctive neural processing stages for pink-masculine stimuli (i.e., in comparison to the other three types of stimuli) in P200, N300, N400 and P600. Overall, our results suggested that pink but not blue was a "gendered" color in Chinese culture. Moreover, our ERP findings contributed to the understanding of the neural mechanism underlying the processing of gender-color stereotypes.